Bioecological Properties of Salvia Officinalis L. - Qodirova Dilbar Normuminovna; Fozilov Sherzod Musurmonovich (Zien Journals, 2022)
Bioecological and morphophysiological features of Salvia officinalis L. in soil-climatic conditions of Surkhandarya region were studied
Keywords: Salvia officinalis L; growth; development; seed count